Efektivitas Metode Mediasi Alternatif Penyelesaian Sengketa Terhadap Kepuasan Para Pihak Dalam Penyelesaian Sengketa Bisnis Di Indonesia - Rafa Ardhian; Rusma Renal Cholif; Togarma Sinaga; Asep Suherman (CV. ITTC INDONESIA, 2025)
Business disputes in Indonesia frequently arise from differences in interests, contract violations, and misunderstandings in the implementation of agreements. Litigation often proves inefficient due to high costs, lengthy processes, and the potential to damage long-term business relationships. Mediation emerges as a more efficient and flexible alternative dispute resolution mechanism, firmly supported by a normative foundation through Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution as well as Supreme Court Regulation Number 1 of 2016. This study aims to analyze the effectiveness of mediation in resolving business disputes, examine the driving and inhibiting factors, and assess its implications for party satisfaction. The findings indicate that mediation can be effective when supported by trust in the mediator, confidentiality of the process, and the willingness of parties to preserve long-term business cooperation, while challenges include the low level of legal awareness, uncooperative attitudes of disputing parties, and the limited availability of competent mediators. In conclusion, mediation has the potential to ensure satisfaction and strengthen substantive justice if implemented optimally, making it a strategic instrument in resolving business disputes in Indonesia.